Emergence of a novel reassortant H3N6 canine influenza virus - Meng, Bo; Li, Hailing; Feng, Chong; Guo, Weiwei; Feng, Yali; Zhu, Dawei; Chen, Hualan; Zhang, Ying (Frontiers in Microbiology, 2023)
Although the nature hosts of Avian influenza viruses (AIVs) are wild bird, multiple subtypes of AIVs have established epidemic in numerous mammals due to their cross-species spillover. Replication and evolution in intermedia mammalian hosts may facilitate AIVs adaptation in humans. Because of their large population and intimacy with human, dogs could act as such intermedia host. To monitor the epidemiology of canine influenza viruses (CIVs) in Liaoning, China, we performed three surveillances in November 2018, March 2019 and April 2019. Five H3N2 and seven novel H3N6 CIVs had been isolated. Since the N6 neuraminidase (NA) genes were clustered with the H5N6 AIV, there’s a high possibility that these H3N6 CIVs were generated from an H3N2 CIVs and H5N6 AIVs reassortment case. Besides that, the H3N6 CIV showed increased mammalian adaptation ability than all the H3N2 strains both in vitro and in vivo study. Even though isolated one month later, the April isolated H3N2 virus replicated more efficiently than the March isolated viruses. Our study indicated that H3 CIVs were undergoing an evolution process, through both genetic mutations and gene reassortment way, at an incredible speed.